2012
DOI: 10.1242/bio.20122790
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic power, huddling and the efficiency of torpor in the South American marsupial, Dromiciops gliroides

Abstract: SummaryDuring periods of cold, small endotherms depend on a continuous supply of food and energy to maintain euthermic body temperature (Tb), which can be challenging if food is limited. In these conditions, energy-saving strategies are critical to reduce the energetic requirements for survival. Mammals from temperate regions show a wide arrange of such strategies, including torpor and huddling. Here we provide a quantitative description of thermoregulatory capacities and energy-saving strategies in Dromiciops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 74 publications
1
16
0
1
Order By: Relevance
“…The influence of social behavior on thermoregulation was also demonstrated by Franco et al. ( 2012 ), who observed higher T b s in Dromiciops gliroides huddling in groups compared with single individuals at 20°C because solitary individuals quickly entered torpor. In our study, irregular evening emergence counts showed that caves were typically inhabited by colonies of 50–100 bats, likely providing Rafinesque's big-eared bats with opportunities for clustering and decreased costs of remaining normothermic.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The influence of social behavior on thermoregulation was also demonstrated by Franco et al. ( 2012 ), who observed higher T b s in Dromiciops gliroides huddling in groups compared with single individuals at 20°C because solitary individuals quickly entered torpor. In our study, irregular evening emergence counts showed that caves were typically inhabited by colonies of 50–100 bats, likely providing Rafinesque's big-eared bats with opportunities for clustering and decreased costs of remaining normothermic.…”
Section: Discussionsupporting
confidence: 59%
“…The presence of a bat colony on roost temperatures is significant, decreasing the amount of energy required to remain normothermic in roosts with temperatures below the thermal neutral zone (Willis and Brigham 2007). The influence of social behavior on thermoregulation was also demonstrated by Franco et al (2012), who observed higher T b s in Dromiciops gliroides huddling in groups compared with single individuals at 20°C because solitary individuals quickly entered torpor. In our study, irregular evening emergence counts showed that caves were typically inhabited by colonies of 50-100 bats, likely providing Rafinesque's big-eared bats with opportunities for clustering and decreased costs of remaining normo- For each variable, roosting structures not sharing common superscript letters for a variable were significantly different at P < 0.05. thermic.…”
Section: Discussionmentioning
confidence: 91%
“…Occasionally, nests are used more than once, although they prefer to build new ones. Based on these observations, Franco et al (2012; and Celis-Diez et al (2012) showed that communal nesting is common in D. gliroides using nest-boxes in two localities of southern Chile (near Valdivia and in Chiloe), with a mean of 2.3 animals per nesting box. Monitoring of nest boxes suggested that D. gliroides is resident throughout the year and uses torpor during cold seasons.…”
Section: Social Thermoregulation and Communal Nestingmentioning
confidence: 91%
“…Not surprisingly, a few heterothermic species, such as small marsupials, bats, rodents and primates, that enter torpor during the cold and/or during periods of food shortages are known to combine both strategies and nest in groups during the torpor season (Fleming, 1980;Vogt and Lynch, 1982;Arnold, 1988;Arnold et al, 1991;Perret, 1998;Blumstein et al, 2004;Séguy and Perret, 2005;McKechnie et al, 2006;Pretzlaff et al, 2010;Franco et al, 2012;Dausmann and Glos, 2014). Well-known examples of social hibernators are marmots (Marmota spp.…”
Section: Introductionmentioning
confidence: 99%